Re-establishment of elephant in the Hluhluwe and Umfolozi Game Reserves, Natal, South Africa - A. Wills (Pachyderm)
Prior to European settlement, when entire populations were decimated elephants were widely distributed throughout Natal and Zululand. Elephants are now protected with the proclamation of the Tembe Elephant Reserve. In line with its policy to re-establish species in conservation areas where they have been eradicated, the Natal Parks Board was motivated to place elephants in the Hluhluwe and Umfolozi Game Reserves which area the largest Reserves in the State. The article discusses the potential problems identified during the planning, and how the monitoring of the programme was conducted in terms of observing movement patterns, feeding behaviour and mortality rate. Thus far the programme, which released 26 animals in Hluhluwe and 30 in Umfolozi and maintains that 18 and 20 are now living in the respective areas, is considered a success.